Inhibitors for Bacterial Cell-Wall Recycling - Yamaguchi, Takao (2012)
Gram-negative bacteria have evolved an elaborate process for the recycling of their cell wall, which is initiated in the periplasmic space by the action of lytic transglycosylases. The product of this reaction, beta-D-N-acetylglucosamine-(1→4)-1,6-anhydro-beta-D-Nacetylmuramyl-L-Ala-gama-D-Glu-meso-DAP-D-Ala-D-Ala (compound 1), is internalized to begin the recycling events within the cytoplasm. The first step in the cytoplasmic recycling is catalyzed by the NagZ glycosylase, which cleaves in a hydrolytic reaction the N-acetylglucosamine glycosidic bond of metabolite 1. The reactions catalyzed by both the lytic glycosylases and NagZ are believed to involve oxocarbenium transition species. We describe herein the synthesis and evaluation of four iminosaccharides as possible mimetics of the oxocarbenium species, and we disclose one as a potent (compound 3, Ki = 300 ± 15 nM) competitive inhibitor of NagZ.